2005
DOI: 10.1097/01.hjh.0000166838.55688.7e
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin B receptor-deficient mice develop endothelial dysfunction independently of salt loading

Abstract: Rescued ETB receptor-deficient mice develop salt-sensitive hypertension. Nevertheless, in this animal model of ETB receptor deficiency, endothelial function is impaired independent of salt-enriched diet or hypertension. This indicates that, in this model, salt-induced hypertension is not mediated by endothelial dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
25
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 36 publications
1
25
0
Order By: Relevance
“…This suggests that the likely target(s) for CD-derived ET-1 in the kidney that determine the salt-sensitive phenotype are ET B located on non-EC, most likely those on inner medullary CD cells. 27 Consistent with previous reports, 26 the salt-sensitive phenotype seems to be independent of endothelial dysfunction resulting from ET B deficiency.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…This suggests that the likely target(s) for CD-derived ET-1 in the kidney that determine the salt-sensitive phenotype are ET B located on non-EC, most likely those on inner medullary CD cells. 27 Consistent with previous reports, 26 the salt-sensitive phenotype seems to be independent of endothelial dysfunction resulting from ET B deficiency.…”
Section: Discussionsupporting
confidence: 81%
“…EC-specific inactivation of ET B results in increased plasma ET-1 concentration and impaired endothelium-dependent vasodilatation but not hypertension. In contrast to models of rescued complete ET B KO 8,26 and CD-specific ET-1 KO, 3 EC-specific KO mice do not demonstrate increased sensitivity to high-salt diets. This suggests that the likely target(s) for CD-derived ET-1 in the kidney that determine the salt-sensitive phenotype are ET B located on non-EC, most likely those on inner medullary CD cells.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Potassium influences the Ca 2ϩ handling by depolarization of the cell membrane of smooth muscle cells in the arterial wall, resulting in vasoconstriction. This simulation of arterial tone is commonly used in other studies on arterial vasoregulation (35)(36)(37). It is unlikely that the induced state of tone will bear impact on the results of insulin-mediated vasoreactivity and PKC activation because we found that insulin-mediated vasodilation is NO dependent and insulin-mediated vasoconstriction is ET-1 dependent.…”
Section: Discussionmentioning
confidence: 60%
“…1 The influence of ET B receptor (ET B R) on arterial pressure (AP) regulation has been more controversial, but the bulk of evidence supports an antihypertensive function. Knockout of the ET B R gene causes salt-sensitive hypertension in rats 2 and mice, 3,4 as does chronic pharmacological blockade of ET B R in a variety of species. [5][6][7][8] One important antihypertensive mechanism associated with ET B R activation may be enhanced renal sodium and water excretion, because renal-collecting, duct-specific knockout of ET B R causes hypertension.…”
mentioning
confidence: 99%